Unknown Article by D.I. Chizhevsky About S.A. Esenin - Ekaterina I. Puzatkina (Studia Litterarum)
The article presents the first complete translation of Dmitry Chizhevsky’s unknown article (from German into Russian) about Esenin’s poem “Song About Bread” (1921), published in 1956 in Chizhevsky’s collection of scientific works. The scholar was the first, who started a deep research of the poem, thus emphasizing its special significance. He analyses the principal motifs of the verse: the “suffering,” martyrdom of bread (grain), and the poisoning of people by the venom accumulated in the bread from the cruelty of the torturers. The first motif refers to the traditions of Old Russian literature and medieval Polish and German poetry. The second one, although it has distant analogies in Slavic and Germanic folklore, is more likely an original creation of the poet, who was under deep impression by murder and torture in his own country. Chizhevsky analyses the “liturgical” symbolism of the poem, the peculiarity of its refraction in the spirit of medieval parodies, and the ambiguous riddles of the Old Believers. The scholar shows Esenin’s creative work in the frame of European spiritual culture. He reveals new sources and roots of Esenin’s imagination, making a significant contribution to understanding the philosophy and culture of the great poet.